2021
DOI: 10.1111/jvs.13081
|View full text |Cite
|
Sign up to set email alerts
|

Revealing floristic variation and map uncertainties for different plant groups in western Amazonia

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The occurrence of C. rubicundus overlaps with these floodplains and the disjunct distribution of this species can be explained by these intense tectonic and sedimentological activities. novaesi is consistent with geological and floristic discontinuities identified in the Juruá river basin (Higgins et al, 2011, Zuquim et al, 2021.…”
Section: Figure 1 Continuous Phylogeographic Reconstruction Of the Di...supporting
confidence: 84%
See 1 more Smart Citation
“…The occurrence of C. rubicundus overlaps with these floodplains and the disjunct distribution of this species can be explained by these intense tectonic and sedimentological activities. novaesi is consistent with geological and floristic discontinuities identified in the Juruá river basin (Higgins et al, 2011, Zuquim et al, 2021.…”
Section: Figure 1 Continuous Phylogeographic Reconstruction Of the Di...supporting
confidence: 84%
“…This ancient Juruá River may have been responsible for speciation, with C. amuna and C. calvus diverging around 0.3 Mya due to geographic isolation on opposite sides of the river. In addition, this region is considered the boundary between the Miocene Pebas (Solimões) Formation, in the west, and the late Miocene-Pleistocene Içá Formation, to the east (Higgins et al, 2011), which is associated with the floristic turnovers zone identified in the Juruá river basin (Zuquim et al, 2021). However, the recent displacement of the Juruá River towards the Jutaí River basin (<0.1 Mya; see Ruokolainen et al, 2020;Rossetti et al, 2021) resulted in the isolation of C. calvus populations from the Jutaí River and the Mamirauá floodplains, and also may have promoted gene flow between C. amuna and C.…”
Section: The Evolutionary History Of Cacajaomentioning
confidence: 99%
“…The complete species turnover occurred within the same vegetation type (evergreen montane forest), as classified in the ecosystem map of Ecuador (Galeas and Guevara 2012). Vegetation classification usually separates floristic units based on species composition and endemism (Borchsenius 1997) and species turnover is more expected between vegetation types (Dambros et al 2020) than within vegetation types (Zuquim et al 2021). Although we did not provide a formal test for a possible mechanistic explanation for the dissimilar fern and lycophyte composition, we cannot discard the hypothesis that specific site conditions were determinant (Kessler and Lehnert 2009), as the 1558-m plot was located in a less exposed area with higher canopy and tree density, while the 2018-m plot was located on a mountain ridge with lower-canopy vegetation, more exposed to weather conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the strength of species–environment relationships varies widely among taxa (Cámara‐Leret et al, 2017). Moreover, environmental determinism in palms is typically weaker than in other plant groups that are less used by humans, including melastomes, ferns and gingers (Tuomisto et al, 2016; Zuquim et al, 2021). Relative to many other plant groups, palms are disproportionately abundant in lowland Amazonia (Muscarella et al, 2020).…”
Section: Introductionmentioning
confidence: 99%